The transient phenomena in the queuing process I - Prohorov, Yu. V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. В. Прохоров. Переходные явления в процессах массового обслуживания I J. Prochorovas. Pereinamieji reiškiniai masinio aptarnavimo procesuose. I